Effects of NSAIDs on the risk factors of colorectal cancer: a mini review. (December 2016) - Hamoya, Takahiro; Fujii, Gen; Miyamoto, Shingo; Takahashi, Mami; Totsuka, Yukari; Wakabayashi, Keiji; Toshima, Jiro; Mutoh, Michihiro
Abstract Evidence from epidemiological and experimental studies has shown that non-steroidal anti-inflammatory drugs (NSAIDs) reduce the risk of colorectal cancer (CRC). The function of NSAIDs and the molecular targets for chemopreventive effects on CRC have been extensively studied and their data were reported. However, the relation between NSAIDs and the risk factors of CRC have not been fully elucidated yet. Thus, relations between NSAIDs and the risk factors of CRC, such as overweight and obesity, alcohol, aging, hypertriglyceridemia and smoking, are summarized with our data and with recent reported data in this review.